Quality checks procedure for erroneous measurements detection of spectral components of solar irradiances (Research, Society and Development, 2022)
The shortwave solar radiation that arrives under the Earth's surface is spectrally composed of the ultraviolet, photosynthetically active, and near-infrared components. Having information about the availability of these parameters in different locations allows public agencies and scientific institutions to plan, execute, and manage energy projects in Brazil. Therefore, this information can be obtained from weather measurements with wide temporal and spatial coverage. However, the solar radiation measuring process is not an easy task, due to the uncertainties caused by instrumentation and operational problems. Thus, the aim of this study was to implement a procedure for erroneous measurements detection of ultraviolet, photosynthetically active, and near-infrared solar irradiances, collected in Botucatu (SP) - Brazil during the years 2001 to 2006, in sub-hourly temporal resolution (5 minutes in Wm-2), to certify the quality of the obtained measured values. For this purpose, analyzes were carried out by two quality check analyzes, the first one to verify whether the measurements were within physically possible limits and the second one whether they were within extremely rare but accepted limits. It was possible to identify that the near-infrared solar irradiance had the highest number of erroneous measurements flagged (0.310% of the total values), followed by photosynthetically active (0.162% of the total values) and, with less flags, from ultraviolet (0.047% of the total values). Measurements of spectral components of solar irradiances that were not flagged as erroneous by the quality checks procedure are considered valid, and can be used in future scientific investigations.